2019
DOI: 10.1159/000499172
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Neuroendocrine Tumours: The Role of Endoscopic Ultrasound Biopsy in Diagnosis and Grading Based on the WHO 2017 Classification

Abstract: Background: One of the controversial issues in the diagnosis of pancreatic neuroendocrine tumours (pNETs) is the accurate prediction of their clinical behaviour. Objectives: The aim of the study was to evaluate the role of endoscopic ultrasound (EUS) biopsy in the diagnosis and grading of pNETs in a certified ENETS Center. Methods: A prospectively maintained database of EUS biopsy procedures was retrospectively reviewed to identify all consecutive patients referred to a certified ENETS Center with a suspicion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 23 publications
(28 reference statements)
1
45
0
Order By: Relevance
“…Hijioka et al reported that the location of the tumor in the pancreatic head and the presence of rich stromal fibrosis negatively affect the sampling adequacy of EUS-FNA [56]. In recent years, fine-needle biopsy (FNB) needles have been used, which are expected to improve diagnostic ability [57][58][59][60][61][62][63].…”
Section: Role Of Eus-fna In Pnensmentioning
confidence: 99%
“…Hijioka et al reported that the location of the tumor in the pancreatic head and the presence of rich stromal fibrosis negatively affect the sampling adequacy of EUS-FNA [56]. In recent years, fine-needle biopsy (FNB) needles have been used, which are expected to improve diagnostic ability [57][58][59][60][61][62][63].…”
Section: Role Of Eus-fna In Pnensmentioning
confidence: 99%
“…This is difficult to translate to cytological samples, since change in architecture in cell block sections will obviously have a significant impact on how mitotic activity will be assessed. In addition, studies on the use of immunohistochemical markers such as ki‐67 on cell blocks is still controversial, with most studies showing good concordance between low‐grade G1 tumors, but underestimation of higher grade lesions . Additional studies with larger comparisons of cell block and resection specimens may be needed to clarify the role of using grading in cytology and a possible incorporation of proposed guidelines in the future versions of classification systems.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Hijioka et al reported that the location of the tumor in the pancreatic head and the presence of rich stromal fibrosis negatively affects the sampling adequacy of EUS-FNA [38]. In recent years, fine-needle biopsy (FNB) needles have been used, which are expected to improve the diagnostic ability [39][40][41][42][43][44][45].…”
Section: Role Of Eus-fna In Pnensmentioning
confidence: 99%
“…However, it is almost impossible to count in 50 HPFs with FNA samples, and the Ki-67 proliferation index is usually used in clinical practice. The concordance rate of the Ki-67 index between PNENs measured from EUS-FNA samples and surgical specimens was reported to be 54%-100% [37,[43][44][45][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] (Table 1), whereas a systematic review reported a rate of 83% [68]. Pooling the data of the studies which compared the Ki-67 LI grades obtained both in EUS-FNA samples and surgical specimen, the concordance rate was 77.5% and the kappa correlation index was 0.65 (95% confidence interval = 0.59 -0.71, P < 0.01) ( Table 2) [37,[43][44][45][49][50][51][52][54][55][56][57][58][59][60][61][62][63][64]…”
Section: Grading Diagnosismentioning
confidence: 99%
See 1 more Smart Citation